Hormonal Regulation of Glucose Kinetics in Rainbow Trout: Effects of Insulin and Glucagon - Forbes, Johnathon (Université d'Ottawa / University of Ottawa, 2019)
Mammals and fish rely on hormones to regulate blood glucose levels. The two major glucose regulating hormones are insulin and glucagon. Literature on mammalian insulin and glucagon is quite extensive, however, there is limited information on how these hormones regulate blood glucose levels in fish. The material available for fish mostly pertains to changes in glucose concentration and gene expression of enzymes, but there is no information on the direct influence they have on glucose kinetics. Therefore, the main goal of my thesis is to measure the change in hepatic glucose production and glucose disposal when rainbow trout are administered insulin or glucagon. The beginning of my research focused on insulin. I hypothesized that rainbow trout respond to insulin by decreasing hepatic glucose production and increase glucose disposal, just like mammals. To test this, I infused insulin for 4 hours at 1.5 g insulin kg 1 min-1. I measured glucose disposal (Rd glucose), hepatic glucose production (Ra glucose), and blood glucose concentration. Following insulin administration the glucose fluxes decreased steadily (Rd glucose -37% and Ra glucose -43%). The decline in blood glucose levels follows the difference between Rd and Ra. These results explain why rainbow trout are unable to clear a glucose load to the same degree as mammals. The second major glucose hormone (glucagon) is what interested me for the second part of the research. The limited information on fish glucagon is even less than that of fish insulin. I speculated that trout respond to glucagon the same way mammals do (increase hepatic glucose production and show no affect on glucose disposal). To study the effects of glucagon on glucose fluxes, I tracked the changes in Ra and Rd glucose. The results showed glucose fluxes showed no siginificant difference from baseline in the first few hours, then steadily decreasing until the final time point reached values below baseline. Therefore, these experiments revealed that glucagon follows a similar pattern of effects in trout as mammals. However, the strength of the response to glucagon is different between trout and mammals. This thesis is the first to investigate the effects of insulin and glucagon on glucose kinetics in rainbow trout. I have concluded that rainbow trout have different responses to insulin and glucagon when compared to mammals. Furthermore, fish showing limited glucoregulatory capacity can be partially explained by their responses to insulin and glucagon.
Keywords: Fish glucoregulation; Insulin; Glucagon; Carbohydrate metabolism; in vivo metabolite fluxes